Ethical Dimensions and Legal Framework in Service Systems: Rights, Obligations, and Business Practices - Syahrial Syahrial; Maya Intan Pratiwi; Samsurijal Hasan; Carlos Barreto (Universitas Negeri Malang, 2026)
This research analyzes the integration of ethical dimensions and legal frameworks within digital healthcare service delivery systems in the era of medical technology transformation. The research used a qualitative methodology with a case study design, performed in XXX City, and included 28 participants including healthcare staff, patients, system administrators, and health legislation specialists. Data was collected via in-depth interviews, focus group discussions, and non-participant observation, thereafter analyzed using thematic analysis. The theoretical foundation of the study is based on the integration of principlism theory, rights-based theory, the technology acceptance model, healthcare economics theory, and sustainable business model theory. The study's findings indicate that the implementation of digital health technology faces considerable challenges in balancing operational efficiency with the protection of patient rights. The findings identify five new dimensions of service provider obligations: digital competence, data management, digital communication, lifelong learning, and digital equity. An analysis of sustainable business methods reveals a tension between profitability, accessibility, and service quality. The research emphasizes the need to redefine patient rights in the digital age, create a comprehensive regulatory framework, and adopt a holistic approach to sustainability that includes the triple bottom line. In Indonesia, including multicultural perspectives, especially Islamic values via the concepts of maslaha and Maqasid Shariah, is essential for developing an ethical and sustainable digital health system.The five theoretical frameworks are integrated through a multi-layered analytical design: principlism provides the ethical foundation; rights-based theory establishes the legal basis for patient rights; TAM explains technology adoption behavior among healthcare providers; healthcare economics contextualizes structural constraints such as market failure and equity gaps; and sustainable business model theory ensures long-term operational viability. Islamic principles were operationalized by applying maslaha (public interest) as an evaluative lens when weighing trade-offs between efficiency and patient welfare, and Maqasid Shariah as a deductive coding framework across five objectives: protection of life, intellect, progeny, wealth, and dignity.